Drivers, Barriers and Impacts of Digitalization on Sustainable Rural Development in Albania - Tomorri, Ilir; Keco, Remzi; Shima, Joana; Tomorri, Kejsi (European Scientific Journal, ESJ, 2025)
The rural sector is one of the most important sectors in Albania, referring to the contribution to economic growth, gross domestic product, and level of employment in the country. Increasing the productivity and performance of agricultural farms, efficiency of resource use, cooperation between small farmers, access to financing, implementation of technology, food quality and safety, are considered some of the main challenges for the sustainable development of this sector. An important instrument to face these challenges is the digitization of this sector, through the use of technology and digital platforms, with the aim of increasing the competitiveness and productivity of agricultural farms. The digitalization process holds the potential to bring about a significant change in how agriculture functions, in terms of tools, technologies, platforms and innovative approaches that support precision agriculture and efficient management of resources, which are essential for agricultural farms in Albania. In this context, the purpose of this paper is to examine the drivers, barriers and impact of digitalization, on the performance of agricultural farms and the sustainable development of the rural sector in our country. In function of the purpose of the study, the questionnaire was designed to collect information from the farmers (interviewers). Based on the data of INSTAT and MARD, for the dominant activities and typology of farms, 938 questionnaires were completed with farmers for the regions selected in the study. The data were analysed and processed with the SPSS program, in accordance with the purpose and research objectives of the study.